Transplanting the great society Lyndon Johnson and Food for Peace - Ahlberg, Kristin L., 1975- (University of Missouri Press, 2008)
"Uses recently declassified sources to trace the successes and limitations of the Johnson administration's efforts to use food aid as a diplomatic tool during the Cold War, both to gain support for U.S. policies and to reward or punish allies such as Israel, India, and South Vietnam"--Provided by publisher.